Peran Layanan Bimbingan Individu Dalam Mengurangi Tekanan Mental Narapidana Perempuan Di Lembaga Pemasyarakatan - Esti Cahya Ningsih; Misrah Misrah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Mental health is physically and psychologically healthy, this greatly affects the health of the individual. The purpose of this study is to describe individual guidance in reducing the mental stress of convicts when carrying out their sentences for mistakes that have been committed in prisons. This study uses a descriptive qualitative method of collecting data through observation and in-depth and structured interviews. Qualitative research is carried out by analyzing phenomena, explaining true events. The results of this study explain that many inmates experience mental pressure, anxiety, anxiety when they have just served their sentence. With the individual guidance carried out by officers can reduce these problems. The form of business is carried out through various activities, approaches. The success of this individual guidance service is very good and increasing every month, through the existing approaches and activities which are very supportive in reducing the mental pressure of female prisoners in prisons.